The role of trehalose-6-phosphate synthase in Arabidopsis embryo development - Gómez, L.D.; Baud, S.; Graham, I.A.
We previously showed that trehalose-6-phosphate synthase 1 (TPS1), which catalyses the first step in trehalose synthesis, is essential for embryo maturation in Arabidopsis [Eastmond, van Dijken, Spielman, Kerr, Tissier, Dickinson, Jones, Smeekens and Graham (2002)Plant J. 29, 225-235]. The tps1 mutant embryos develop more slowly than wild type. Patterning in the tps1 embryos appears normal but they do not progress past the torpedo stage to cotyledon stage, which is when storage reserves start to accumulate in the expanding cotyledons. Our initial data led to the hypothesis that trehalose metabolism plays a key role in regulating storage reserve accumulation by allowing the embryo to respond to the dramatic increase in sucrose levels that occurs at the torpedo stage of embryo development. More recent data demonstrate that while the tps1 mutant is blocked in the developmental progression of embryos from torpedo to cotyledon stage the expression of genes involved in the ccumulation of storage reserves proceeds in a similar fashion to wild type. Thus it appears that induction of metabolic processes required for accumulation of storage reserves in tps1 occurs independently of the developmental stage and instead follows a temporal programme similar to wild-type seeds in the same silique.